Overconfidence and Investment Decisions A Descriptive Study of the Literature from a Behavioral Finance Perspective - Salis, Mochamad Ikhsan; Situngkir, Tiar Lina; Apriyanti, Ariska; Khotimah, Novy Fitri (Yayasan Riset dan Pengembangan Intelektual, 2024)
Investment has become a crucial part of modern economic life. Over time, there has been an increase in investment participation, along with several challenges related to investor behavior. This study aims to examine the impact of overconfidence on investment decision-making, analyzed using a descriptive qualitative research method through a literature review within a behavioral finance perspective. Overconfidence is a condition of excessive belief in one’s abilities and knowledge, often causing investors to overlook actual risks and have unrealistic return expectations. This phenomenon can lead to mistakes in risk management and suboptimal investment decisions. The study finds that overconfidence is frequently experienced by Generation Z, who have quick and easy access to information and financial markets through digital platforms. The study concludes that overconfidence has a significant impact on investment decisions and may result in long-term losses. To mitigate the negative effects of overconfidence, investors are advised to be aware of their cognitive biases and adopt a data-driven approach in their decision-making.